37 Clinical workload in a DMP in the first three months post discharge and comparison of hfref and HFpEF. (7th October 2015) - Murphy, T; Watershouse, D; James, S; O'Hanlon, R; Gallagher, J; Legwidge, M; McDonald, K; Kenny, C
Abstract : Background: Continuing high event rates post discharge following management of acute decompensated heart failure (HF) may reflect the lack of uniform application of proven benefit of disease management programmes (DMP). Compromising the application may be the workload associated with this approach, which has not been adequately described. Methods: All patients admitted with a primary diagnosis of HF were enrolled in a comprehensive DMP encompassing in-patient and out-patient care. Workload was viewed through an assessment of post discharge clinic visits (scheduled and unscheduled), telephonic contact and medication changes. Outcomes measured were mortality and emergency hospitalisations. Results: 1292 patients were enrolled (male 58.7%; 74.5 yrs; HFrEF 68%). Mortality at one and three months post discharge was 0.3% and 3.8% respectively, with HF readmission of 2.5% and 7.3% respectively. Over the three-month programme duration, there were 5046 clinical visits, with a mean of 3.9 visits/patient, and 0.47 unscheduled visits/patient. Almost 30% of patients required at least one unscheduled visit, most frequently in the first week post discharge. Those with HFrEF had more frequent visits than the HFpEF cohort (4.0 vs. 3.7 visits/patient), which likely reflects increased number of medication titrations. There was a mean of 12.7 calls/patient with outbound calls being dominant. 25.8% of patients had 1 inbound call and 45.7% of patients had >1 during this three-month period. There no differences in frequency of inbound and outbound calls in those with HFrEF vs. those with HFpEF. At discharge, 92.5% of patients were prescribed diuretics. Mean diuretic dose at discharge was 58.7 mg frusemide eq. Mean diuretic dose at three months being 63.1 mg. Alteration of diuretic dose (at least one increase or decrease) occurred in 44.7% of patients with 25.8% having one dose change and 18.9% having >1 dose changes during the three-month programme duration. There was no significant difference in diuretic dose between those with HFrEF vs. HFpEF at either discharge or three months. At discharge 73.7% of the patients were prescribed ACEi with at least one dose alteration in ACEI / ARB occurring in 31.9% during the programme. Dose changes in ACEi/ARB were less common in the HFpEF group but still occurred in approximately 20% of those on an ACEi. At discharge, 67.7% were prescribed beta-blockers, with doses unchanged at 3 months in 57.2%. Epleronone as prescribed in 8.8% on discharge, and in 12.4% at three months, with a mean dose of 24.1 mg. Conclusion: The workload associated with an intensive cardiology-led DMP in the immediate period post discharge, while significant, reflecting clinical instability and complexity of care, is similar for those with both HFrEF and HFpEF. Given the rapid growth in this patient population, this data should be used to inform appropriate resource organisation for establishing or evolving DMP structures.